Towards sustainable, low methane rice production in Latin America - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2024)
The document provides detailed information about a project aimed at promoting sustainable low-methane rice production in Latin America. It focuses on countries such as Brazil, Chile, Ecuador, and Uruguay, with the goal of identifying strategies to reduce methane emissions in rice agriculture. The project aims to overcome barriers such as perceptions of high risk, lack of data on rice varieties with lower methane emissions, suboptimal irrigation management, weed control, and the lack of enabling business models and public policies. The importance of working collaboratively between countries to achieve a transition towards sustainable, low-methane rice production is emphasized.